Domestic wastewater treated with Sagittaria latifolia in constructed wetlands - Gaspar López-Ocaña; Anel Magaña-Flores (Dyna, 2023)
Constructed wetlands are viable alternatives for the removal of multiple pollutants. The performance of Sagittaria latifolia in free flowing and subsurface wetlands in removing pollutants from domestic waters was evaluated. 12 wetlands will be followed, three free with species and three without species, three subsurface with species and three without species, with retention times of 6.7 days for the free and 3.5 days for the subsurface. The subsurface with species presented an effluent with turbidity of 4.4±0.8 NTU, color of 143.9±27.4 UC and 33.9±25.7 mgL-1 of COD. The free samples with species presented turbidity of 10.1±2.8 NTU, color of 346.3±87.0 UC and 74.7±30.0 mgL-1 of COD. The wetland with the best performance was the subsurface with species, eliminating turbidity, color, and COD in 95.9, 89.4, 95.7% respectively, obtaining a COD kinetic coefficient of 0.34 (free flow) and 0.89 days-1 (subsurface).